Monitoring job search effort with hyperbolic time preferences and non-compliance: A welfare analysis - Bart Cockx; Corinna Ghirelli; Bruno Van der Linden (Institute for the Study of Labor (IZA), 2013)
This paper develops a partial equilibrium job search model to study the behavioral and welfare implications of an Unemployment Insurance (UI) scheme in which job search requirements are imposed on UI recipients with hyperbolic preferences. We show that, if the search requirements are well chosen, a perfect monitoring scheme can in principle increase the job finding rate and, contrary to what happens with exponential discounting, it can raise the expected lifetime utility of the current and future selves of sophisticated hyperbolic discounters. The same holds for naive agents if the welfare criterion ignores their misperception problem. In sum, introducing a perfect monitoring scheme can be a Pareto improvement. However, if claimants have the opportunity to withdraw from the UI scheme, their long-run utility can even be lower than in the absence of job search requirements. Imperfections in the measurement of job-search effort further reduce the chances that monitoring raises the welfare of the unemployed.
Keywords: D60; D90; J64; J65; J68; 330; job search model; job search monitoring; non-compliance; hyperbolic discounting; social efficiency